Model charged cylindrical nanopore in a colloidal dispersion: charge reversal, overcharging and double overcharging - González-Tovar, E.; Lozada-Cassou, M. (Condensed Matter Physics, 2017)
Using the hypernetted-chain/mean spherical approximation (HNC/MSA) integral equations we study the electrical double layer inside and outside a model charged cylindrical vesicle (nanopore) immersed into a primitive model macroions solution, so that the macroions are only present outside the nanopore, i.e., the vesicle wall is impermeable only to the external macroions. We calculate the ionic and local linear charge density profiles inside and outside the vesicle, and find that the correlation between the inside and outside ionic distributions causes the phenomena of overcharging (also referred to as surface charge amplification) and/or charge reversal. This is the first time overcharging is predicted in an electrical double layer of cylindrical geometry. We also report the new phenomenon of double overcharging. The present results can be of consequence for relevant systems in physical-chemistry, energy storage and biology, e.g., nanofilters, capacitors and cell membranes. Використовуючи гiпернет-ланцюгове/середньо-сферичне наближення iнтегральних рiвнянь, ми вивчаємо подвiйний електричний шар всерединi i зовнi модельної зарядженої цилiндричної бульбашки (нанопори), зануреної в примiтивну модель розчину макроiонiв таким чином, що макроiони присутнi лише зовнi нанопори, тобто стiнка бульбашки є проникною лише для зовнiшнiх макроiонiв. Ми обчислюємо профiлi iонної густини i локальної лiнiйної зарядової густини всерединi i зовнi бульбашки i знаходимо, що кореляцiя мiж внутрiшнiм i зовнiшнiм розподiлами спричинює явище надмiрного зарядження (також вiдоме як збiльшення поверхневого заряду) i/або зарядоiнварiантнiсть. Це вперше, коли явище надмiрного зарядження прогнозується в електричному подвiйному шарi цилiндричної геометрiї. Ми також повiдомляємо про нове явище подвiйного надмiрного зарядження. Представленi результати можуть мати значення для пов’язаних систем у фiзичнiй хiмiї, для збереження енергiї, в бiологiї, а саме, для нанофiльтрiв, конденсаторiв i клiтинних мембран.